Delineation of single-cell Altas provides new insights for development of coronary artery lesions in Kawasaki disease: bad and good signaling molecules - Lin, Qiuping; Lv, Xin; Qiu, Qingzhu; Mei, Lianni; Chen, Liqin; Song, Sirui; Liu, Wei; Jiang, Xunwei; Huang, Min; Shen, Libing; Xiao, Tingting; Xie, Lijian (Frontiers in Pediatrics, 2025)
BackgroundKawasaki Disease (KD) is a vasculitis syndrome featured with a high and persistent fever in children. It is the leading cause of coronary artery lesions (CALs) for children in developed countries.MethodsSingle-cell RNA sequencing analyses were performed for the peripheral blood mononuclear cells from three KD non-CAL patients before/after IVIG treatment (KD BT and KD AT), three KD CAL patients before IVIG treatment (CAL BT), and three KD CAL patients after IVIG treatment (CAL AT).ResultsOverall expression analyses show immunoglobulin and adaptive immunity related genes are commonly upregulated in CAL BT and AT patients while antimicrobial and innate immunity related genes are commonly downregulated in them. Pseudo-time analyses demonstrate that CAL BT patients have a disorganized cell development trajectory with multiple overlapped cell linages and CAL AT patients have a dysregulated B cell developmental trajectory featured with a mixed monocyte and B lineage. In gene branch pseudo-time analyses, the repressed expression of SPI1 and MT2A are found in CAL BT patients, which is similar to their expression patterns in KD BT patients; while the early elevated expression of SPI1 and MT2A could partly explain the dysregulated B cell development in CAL AT patients. Cell communication analyses demonstrates that CAL BT patients have the lower number of inferred cell-to-cell interactions and the weakest interaction strength among four groups, whereas CD14 monocytes in CAL AT and KD BT patients have strong cell-to-cell interaction strength which may contribute to CAL or KD pathogenesis. In the monocytes of CAL patients, MCH-II is a significantly increased signal and RESISTIN is a significantly decreased signal compared to non-CAL counterpart.ConclusionsOur results suggest that MCH-II is a bad signal for indicating CAL development while RESISTIN is a good signal for protecting from CAL development.